Dimitri wants to become a Chef: An inclusive tool (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
In this workshop, attendees discovered a fun and inclusive tool for exploring the concept of open recognition with everyone. "Dimitri Wants to Become a Chef" is written in easy-to-read and understandable language (It is Facile à Lire et à Comprendre (FALC) in French.) The tool allows you to discuss recognition, particularly with allophones or people with intellectual disabilities. The players followed the story of Dimitri who is working as a plumber and wants to become a chef. To apply to a cooking school, he must provide testimonials. Players are invited to read these testimonials and choose which ones to present to the recruiter Léane, which ones to throw in the trash, etc. This playful tool allows players to explore non-formal and informal recognition.This game is available only in English here:https://www.laboite-a.fr/produit/dimitri-veut-devenir-cuisinier/ >This workshop was also an opportunity to discuss the benefits of creating inclusive tools and games to make sure everyone can access recognition.Keywords: informal and formal recognition, open recognition, tools for recognition